Direct observation of pore collapse and tensile stress generation on pore walls due to salt crystallization in a PDMS channel. Issue 22 (24th May 2019) - Naillon, Antoine; Joseph, Pierre; Prat, Marc
Abstract : In contrast with the classical picture where the generation of stress on pore walls due to salt crystallisation is analysed by a compressive stress using the concept of crystallization pressure, we report a mechanism leading to the generation of a local tensile stress. Abstract : The generation of stress on pore walls due to salt crystallization is generally analysed as a compressive stress generation mechanism using the concept of crystallization pressure. We report on a completely different stress generation mechanism. In contrast with the classical picture where the crystal pushes the pore wall, the crystal growth leads to the generation of a local tensile stress. This tensile stress occurs next to a region where a compressive stress is generated, thus inducing also shear stresses. These findings are obtained from direct optical observations in PDMS model pores where the tensile stress generation results in the collapse of the pore region located between the crystal and the pore dead-end. The experiments also reveal other interesting phenomena, such as hyperslow drying in PDMS channels or asymmetrical growth of the crystal during the collapse.